(untitled) (World Bulletin of Public Health, 2024)
Anemia is a multifaceted concern in patients with diffuse toxic goiter, commonly known as Graves’ disease. This review aims to consolidate existing knowledge regarding the prevalence, etiology, and clinical course of anemia in individuals with diffuse toxic goiter. Through an extensive literature search, we explore the complex interplay between thyroid dysfunction and anemia, encompassing various mechanisms such as increased metabolic demand, malabsorption, autoimmune processes, medication side effects, and associated comorbidities. We discuss the diverse manifestations of anemia in diffuse toxic goiter, including iron deficiency, pernicious anemia, autoimmune hemolytic anemia, and bone marrow suppression. Furthermore, we elucidate the diagnostic challenges and prognostic implications associated with anemia in this context. Importantly, we underscore the necessity of vigilant screening, appropriate diagnostic evaluation, and tailored management strategies to effectively address anemia and optimize clinical outcomes in patients with diffuse toxic goiter. By synthesizing current evidence, this review provides valuable insights into understanding and managing the course of anemia in the context of diffuse toxic goiter.